Evidence for Nuclear Control of the Expression of the atpA and atpB Chloroplast Genes in Chlamydomonas. - Drapier, D (1992)
We analyzed three nuclear mutants of Chlamydomonas reinhardtii altered in the expression of the chloroplast genes atpA or atpB coding for the [alpha] or [beta] subunit of the chloroplast ATP synthase. These mutants revealed the existence of three nuclear products controlling the expression of the two chloroplast genes: the first one acts on the translation of the atpA transcript, and the two others act specifically on the stability of either the atpB or the atpA mRNAs. The nuclear mutation responsible for the decreased stability of the atpB mRNA prevented translation of the corresponding polypeptide. In contrast, the mutation responsible for the decreased stability of the atpA mRNA had limited effect on the translation of the [alpha] subunit, thereby allowing its accumulation and assembly in an active ATP synthase. Although acting originally on the expression of only one of the two main coupling factor 1 subunits, the three mutations caused a change in the translation rate of the other subunit, as viewed in 5-min pulse labeling experiments. This is indicative of a concerted expression of the [alpha] and [beta] subunits at an early post-translational step, or during translation, that may be critical for the assembly of the chloroplast ATP synthase.